Interaction between non-uniform flows in a gas of rough spheres - Gordevskyy, V. D.; Sysoyeva, Yu. A. (Математическая физика, анализ, геометрия, 2002)
For the model of rough spheres the bimodal distribution with inhomogeneous but stationary Maxwellians is considered. It approximately describes the interaction between two flows, which can rotate as a rigid body about the immovable axes. Conditions ensured the infinitesimality of the uniformintegral remainder for the accordant Boltzmann equation are obtained.